Temporomandibular Joint Disorders: A Report of Urhobo Patients in Abraka, Nigeria - Ese, Anibor; Brenmound, Jones Dibie; Osaretin, Mabiaku Yvonne; Chiamaka, Igwilo (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2021)
This study reconnoitered Temporomandibular Joint Disorders among the Urhobos in Abraka, Nigeria. The cross sectional study design was adopted for this study, and the cluster sampling technique was employed. Data was collected with the aid of a well-structured questionnaire. Ethical clearance was obtained from the Research and Ethics Committee of the Department of Human Anatomy and Cell Biology, Delta State University, Abraka before data collection Data obtained was subjected to Statistical Package for Social Sciences (SPSS version 25) for the purpose of analysis. This study made use of three hundred and eighty-five subjects (57% female and 43% male). The causes of temporomandibular joint disorders include accidents, assault, road traffic accidents, and falls. Temporomandibular joint disorder pointers ranged from pain in or around the ear, followed by pain when chewing, limited mouth opening, noise within temporomandibular joint when opening and closing the jaw, and jaw locking. Based on associated reasons for temporomandibular joint disorder, prior injury to the head and neck had the highest frequency. Significant gender difference was seen in the pointers of temporomandibular joint disorders (p<0.05). The most frequent indicator of temporomandibular joint disorders among the Urhobo males scrutinized is limited mouth opening, while for the Urhobo females it is prior injury to the head and neck.